War and society in Afghanistan from the Mughals to the Americans, 1500-2013 - Roy, Kaushik 1971- (Oxford University Press, 2015)
This monograph analyses the rhythms of war and the geopolitical significance of Afghanistan with a focus on the interrelated concepts of weak/rentier state, great power rivalry and counter-insurgency. It analyses why the Mughal, the British, the Soviets, and the Americans won the conventional wars in Afghanistan but were defeated in the unconventional ones. It takes a comprehensive view of the history of the region and provides a political and military narrative of conventional andunconventional war in Afghanistan during the last five centuries.